The Transformation Of E-HRM In Developing The Quality Of Human Resources Based On Information Technology Toward Employee Performance Through Employee Satisfaction - Sumaryono, Sumaryono; Machdar, Nera Marinda; Hidayat, Wastam Wahyu; Rony, Zahara Tussoleha (Universitas Dharma Wacana, 2025)
This research aims to evaluate the impact of e-compensation, e-learning, and e-performance appraisal on organisational performance, with team member satisfaction as a mediating variable. The study was conducted at PT. XYZ. Methodology used: A total of 77 respondents participated in this research. Data processing was carried out using the Structural Equation Modeling (SEM) method with a Partial Least Squares (PLS) variance-based approach. The results of the reliability and construct validity tests indicate that all variables have a high reliability level, with Cronbach's Alpha values as follows: Compensation Management (0.96), E-Learning (0.95), Employee Satisfaction (0.94), Employee Performance (0.96), and Performance Appraisal (0.91), all of which exceed the threshold of 0.90. The team member satisfaction variable consists of 13 indicators (Z.01 to Z.13) and was measured using a survey involving 77 respondents. To meet the criteria for convergent validity, each item must have a loading factor value of at least 0.60. An R-square value of 0.81 indicates that 81% of the variability in the dependent variable. Based on the analysis results, all indicators in this study meet the criteria for good validity and reliability. The indicators for the Employee Satisfaction variable show loading factor values above the threshold of 0.60.